PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI PUSAT GROSIR CILILITAN - Kasmanto Miharja (MIX: Jurnal Ilmiah Manajemen, 2015)
Abstract: The research was conducted at PT. Prima Graha Citra as an organizer of Pusat Grosir Cililitan. The purpose of this study was to determine the effect of the marketing mix on purchase decisions stall/ counter in Pusat Grosir Cililitan Navel either partially or jointly. The method in this study using simple linear regression analysis to determine the effect of each independent variable on the dependent variable and Multiple Linear regression analysis to determine the effect of independent variables on the dependent variable simultaneously.The results of a simple linear regression analysis states that each independent variable affects the dependent variable to see t count greater than t table and the level of influence of each with respect to the value of the coefficient of determination with the help of SPSS. Multiple linear regression analysis also showed that all independent variables jointly affect the dependent variable to see if the value of the coefficient of determination results data using SPSS. Key words: marketing mix, Purchase Decision, determinantion, coefficient.